2017
DOI: 10.20959/wjpr20178-8750
|View full text |Cite
|
Sign up to set email alerts
|

Study of Effectiveness and Resistance of Various Toothpaste on Mouth Microbial Flora

Abstract: There are various toothpastes, which are used for brushing the teeth in different parts of the world. Several studies have been reported on the resistance and effectiveness of toothpastes on oral bacteria. This study was conducted to evaluate the resistance and effectiveness of various class of toothpastes on oral microflora. The present study was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…The two natural/herbal toothpastes Tb1 and Tb2 displayed the highest effectiveness activity of 87.5% respectively. This is similar to the findings of Shweta et al, (2017) and could be attributed to the presence of herbal ingredients like Babool and Neem extracts in natural/herbal tooth pastes (Sharma et al, 2014) as these extracts have been shown to possess astringent and antiseptic activity (Lakshmi et al, 2015) and have also been shown to be very effective at treating and preventing dental infection (Bhambal et al, 2011). The study also revealed that the chemical toothpastes Tb4 and Tb5 exhibited effectiveness activity of 75.0% and 62.5% respectively while the lowest percentage of effectiveness activity of 25.0% was exhibited by the chemical toothpaste Tb3.…”
Section: Resultssupporting
confidence: 92%
“…The two natural/herbal toothpastes Tb1 and Tb2 displayed the highest effectiveness activity of 87.5% respectively. This is similar to the findings of Shweta et al, (2017) and could be attributed to the presence of herbal ingredients like Babool and Neem extracts in natural/herbal tooth pastes (Sharma et al, 2014) as these extracts have been shown to possess astringent and antiseptic activity (Lakshmi et al, 2015) and have also been shown to be very effective at treating and preventing dental infection (Bhambal et al, 2011). The study also revealed that the chemical toothpastes Tb4 and Tb5 exhibited effectiveness activity of 75.0% and 62.5% respectively while the lowest percentage of effectiveness activity of 25.0% was exhibited by the chemical toothpaste Tb3.…”
Section: Resultssupporting
confidence: 92%